Oncogenic role of RARG rearrangements in acute myeloid leukemia resembling acute promyelocytic leukemia - Feng Wang; Luyao Zhao; Yun Tan; Xufeng Cen; Huan Gao; Huimin Jiang; Ying Liu; Yunxuan Li; Tingting Zhang; Chenxi Zhao; Ting Shi; Guilin Xu; et al. (Nature Communications)
Abstract Acute myeloid leukemia (AML) featuring retinoic acid receptor-gamma (RARG) rearrangements exhibits morphological features resembling those of acute promyelocytic leukemia but is associated with drug resistance and poor clinical outcomes. However, the mechanisms underlying the role of RARG fusions in leukemogenesis remain elusive. Here, we show that RARG fusions disrupt myeloid differentiation and promote proliferation and self-renewal of hematopoietic stem and progenitor cells (HSPCs) by upregulating BCL2 and ATF3. RARG fusions overexpression leads to preleukemic phenotypes but fails to induce oncogenic transformation. However, the co-occurrence of RARG fusions and heterozygous Wt1 loss induce fully penetrant AML by activating MYC and HOXA9/MEIS1 targets. Leveraging Connectivity Map resources and high-throughput screening, we identify venetoclax, homoharringtonine, and daunorubicin as potential therapeutic options for RARG-AML. Overall, our findings provide pivotal insights into the molecular mechanisms governed by RARG fusions and enhanced by WT1 loss in AML development and propose a rational therapeutic strategy for RARG-AML.